2018
DOI: 10.1016/j.jpor.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Self-etching ceramic primer versus hydrofluoric acid etching: Etching efficacy and bonding performance

Abstract: Under limited conditions, using MEP resulted in comparable SBS results to HFMP; meanwhile HFMP remains the gold standard for pretreatment of glass ceramics for resin-luting cementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
121
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 22 publications
27
121
2
6
Order By: Relevance
“…A study with AFM images of the IPS Empress 2 presented results similar to ours, showing surface irregularities with peaks and valleys after the acid etching with HF acid 5% 43 . Similar results were found in others studies 12,41,42 ,using AFM images showing higher peaks and deeper valleys after HF acid etching at 10% during 20s, what may have increased the rougness of the IPS e.max CAD.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A study with AFM images of the IPS Empress 2 presented results similar to ours, showing surface irregularities with peaks and valleys after the acid etching with HF acid 5% 43 . Similar results were found in others studies 12,41,42 ,using AFM images showing higher peaks and deeper valleys after HF acid etching at 10% during 20s, what may have increased the rougness of the IPS e.max CAD.…”
Section: Discussionsupporting
confidence: 91%
“…For restorations with glass-ceramic and success bonding with composite resin cements, the use of hydrofluoridric acid (HF) etching is recommended 30,31 . HF modifies the ceramic surface, because the acid removes the glassy matrix, exposes crystalline structure 12,32 , increases the roughness 11 and surface energy 13 in acidsensitive ceramics, as lithium disilicate 33 , forming hexafluorosilicates 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the manufacturer, these novel material reduces the toxic potential of the HF, the chair-time required and the technique sensitivity of etching ceramic when compared to the conventional methods (9). It was shown that the selfetching ceramic primer promotes less-pronounced etching pattern than that produced by the two-step procedure involving hydrofluoric acid and silane (10,11).…”
Section: Introductionmentioning
confidence: 99%